Analysis of eating disorders, emotional eating and depression levels in individuals diagnosed with substance use disorder - Aygül, Irmak; Şahin, Muzaffer; Ünübol, Başak (Journal of Dependence, 2023)
Objective: The aim of this study to examine the relationship between substance use disorder, emotional eating, eating disorders and depression. Method: Data were collected from 100 people for control group and 100 people who receiving outpatient or inpatient treatment with the diagnosis of Substance Use Disorder, a total of 200 people. The study was carried out at the S.B.U Erenköy Psychiatric and Neurological Diseases Training and Research Hospital. Results: According to the demographic data results obtained in the study, the density is between (37%) the ages of 2837 in whole sample. The education level, being married and having children, lastly the rates of got a psychiatric-psychological treatment were lower in individuals with substance use disorder. Emotional eating, developing an eating disorder and depression level predict 84.8% of substance use severity. A positive and statistically significant difference was found between severity of substance use to emotional eating, developing an eating disorder and depression level. Conclusion: Emotional eating, developing eating disorders and depression levels are higher in individuals with diagnosed with substance use disorder than healthy individuals. In the addiction treatment process, it is important to consider other pathologies such as emotional eating and eating disorders.